Identifying the potential of ovalbumin and its’ hydrolysates to be used in a liquid food system to develop functional beverages - Maggonage Hasini Udeshika Maggonage; Prabudhdha Manjula; Edirisingha Dewage Nalaka Sandun Abeyrathne; Dewei Shu; Xi Huang; Dong Uk Ahn (Poultry Science)
Ready-to-drink protein beverages have gained attention in the functional beverage market. This study examined the possibility of using ovalbumin and its hydrolysates to develop functional protein beverages. Lyophilized ovalbumin (5%, w/v) was dissolved in distilled water (pH 10) with sugar, salt, and vanilla and pasteurized at 56.7°C for 3.5 min to prepare a basal ovalbumin beverage (OVA). The beverages were sequentially hydrolyzed using pepsin (pH 2.5, 37°C for 3 h) first, then with protease (pH 6.5, 37°C for 3 h), or protease (pH 6.5, 37°C for 3 h) followed by trypsin (pH 7.8, 37°C for 3 h) combinations. Three beverages (OVA, PrTr, and PePr) were tested for physical, functional, and quality characteristics. Complete hydrolysis by enzyme combinations was ensured using 15% SDS-PAGE. Enzymatic hydrolysis caused an increase in the solubility of ovalbumin in water. The beverages showed antioxidant activity, and hydrolyzed drinks showed antimicrobial activity. No significant difference in acidity, but a reduction in pH, an increase in TSS, and alterations in viscosity were observed among the drinks with storage. A significant difference (p < 0.05) in titratable acidity was identified between the two hydrolyzed drinks, but no difference (p > 0.05) within a treatment was observed until Day 14. In conclusion, ovalbumin and its hydrolysates have the potential for preparing functional protein beverages with a shelf-life of up to 7 days.